Re-Branding Produk Sebagai Daya Tarik Pemasaran pada UMKM Jamu di Dusun Kedurus Kabupaten Sidoarjo - Pratiwi, Laras Reynard; Putri, Lidzikirllah Fannayu; Wati, Deby Fatimah; Wulandari, Ria (Universitas Nusantara PGRI Kediri, 2023)
Instant herbal medicine is one of the UMKM goods created by the people of Dusun Kedurus. The label on the plastic standing pouch that holds the powder form of jamu indicates that it is a herbal version. The label's appearance is quite straightforward, with only the name and effectiveness of the herbal medicine listed, and no further details like composition, presentation style, expiration date, or halal logo. Ineffective labeling may have an effect on the sales process by lowering buyer confidence. The goal of this initiative is to modernize the marketing and labeling of herbal medicines. In addition to receiving assistance with labeling, managing NIB (business identification number), SNI (Indonesian national standard), SPPL (statement of ability to manage and monitor environment), and creation of a social media account, herbal medicine managers also take part in socialization activities. The outcomes of this effort include a more appealing label for herbal medication, applications for NIB, SNI, SPPL, and social media marketing for herbal medicine.